2011
DOI: 10.1016/j.neuroimage.2010.09.053
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of noise-normalized minimum norm estimates for MEG analysis using multiple resolution metrics

Abstract: Noise-normalization has been shown to partly compensate for the localization bias towards superficial sources in minimum norm estimation. However, it has been argued that in order to make inferences for the case of multiple sources, localization properties alone are insufficient. Instead, multiple measures of resolution should be applied to both point-spread and cross-talk functions (PSFs and CTFs). Here, we demonstrate that noise-normalization affects the shapes of PSFs, but not of CTFs. We evaluated PSFs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
227
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 182 publications
(238 citation statements)
references
References 30 publications
11
227
0
Order By: Relevance
“…These discrepancies with respect to the present results most likely reflect the very different spatial specificities ECoG vs. MEG. Whereas ECoG LFPs reflect localized current sources on a millimeter scale, inverse source localization in MEG is uncertain by several centimeters (Hauk et al, 2011). Moreover, MEG is insensitive to radial current (Mosher et al, 1992), which is the likely principal source of ECoG potentials (Buzsaki et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These discrepancies with respect to the present results most likely reflect the very different spatial specificities ECoG vs. MEG. Whereas ECoG LFPs reflect localized current sources on a millimeter scale, inverse source localization in MEG is uncertain by several centimeters (Hauk et al, 2011). Moreover, MEG is insensitive to radial current (Mosher et al, 1992), which is the likely principal source of ECoG potentials (Buzsaki et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…EEG/MEG source estimates not only have limited spatial resolution compared with fMRI localizations but may also be systematically biased (e.g., to locations closer to the sensors for classical minimum norm estimation; Hauk, Wakeman, & Henson, 2011;Lin et al, 2006;Fuchs et al, 1999). A direct translation of fMRI coordinates to our source space is therefore not recommended.…”
Section: Roi Analysismentioning
confidence: 99%
“…We would like to point out that effects in these ROIs do not necessarily reflect activity in exactly that location but could also reflect processes in their vicinity, and in particular more medial or deeper areas. However, this ambiguity is inherent to EEG and MEG data (Hauk et al, 2011;Fuchs et al, 1999).…”
Section: Roi Analysismentioning
confidence: 99%
“…In fact, we first 445 apply wMNE to single ICs, and then we linearly recombine the source spaces, which has been 446 proven to be a more effective strategy then the reverse order (linear recombination followed by 447 wMNE) (Mantini et al, 2011). A possible reason might be that source estimates of single or double 448 sources could be more reliable than multiple simultaneously active sources (Darvas et showed that for neighbouring voxels distant at least 3.2 cm the relative dependence is highlyliterature (Hauk et al, 2011). Now, in this study we discuss regions, involved in OBS and EXE, 456 which are closer than this distance.…”
Section: Paradigm 421mentioning
confidence: 99%